The Strait Of Tiran And Its Impact On Egyptian Relationship With Saudi Arabia And The Zionist Entity - ديوب محمد; زم بسيمة (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The strait of Train is one of the most important waterways, this importance has increased in light of its great impact on the mutual relations between Egypt and Saudi Arabia on one hand and between Egypt and Israel on the other. And in this context we find that the common interests of neighboring countries have determined the nature of the relations between them through the study of political and economic relations between these countries by the strait and after, and indicate the impact of the straits of Tiran on bilateral relations between countries. Results of the study showed that the Tiran is one of the waterways that dominate bilateral relations between neighboring countries, It also showed that the understanding of the Egyptian and Saudi sides regarding placing the islands of Tiran and Sanafir under the Egyptian tutelage made the Tiran pass a regional corridor and Egypt’s dominance of the strait status before the Camp David agreement, After the Camp David agreement and through article 5 and considering the strait as an international passage, Egyptian hegemony turned into Israeli hegemony, Also, Israel eliminated the need for its ships to pass through the Suez canal after the Camp David agreement. The study recommended the necessity of strengthening the understanding between Egypt and Saudi in reconsidering the status of the strait of Tiran and considering it a regional passage to enhance Egypt’s control over the strait, Also strengthening the Egyptian- Saudi relations for the benefit of the two countries, and to reconsider the Egypt Israel peace treaty.